1986
DOI: 10.1161/01.atv.6.2.146
|View full text |Cite
|
Sign up to set email alerts
|

Injury and repair of endothelium at sites of flow disturbances near abdominal aortic coarctations in rabbits.

Abstract: The acute and chronic effects of flow disturbances on arterial endothelium were studied by locally constricting the diameter of the rabbit abdominal aorta by 62% + 2.4% (mean ± SE). This procedure produced a region of elevated shear stress immediately upstream from the coarctation. A region of small irregular vortices was formed in the first 5 to 7 mm downstream, whereas an annular vortex was observed in the region from 2.0 to 2.5 cm further downstream. Morphologic changes to the endothelium near these coarcta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(54 citation statements)
references
References 20 publications
1
53
0
Order By: Relevance
“…Endothelial cells showed distinct changes that are known to be induced by elevated WSS, - 40 such as protrusion and increased cell density near the border of desquamation, where a very high WSS was expected, even 8 weeks after operation. However, these changes became indistinct in the proximal segment near the aortic orifice of the same flow-loaded CCA, where elevated WSS was considerably reduced due to luminal dilatation.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cells showed distinct changes that are known to be induced by elevated WSS, - 40 such as protrusion and increased cell density near the border of desquamation, where a very high WSS was expected, even 8 weeks after operation. However, these changes became indistinct in the proximal segment near the aortic orifice of the same flow-loaded CCA, where elevated WSS was considerably reduced due to luminal dilatation.…”
Section: Discussionmentioning
confidence: 99%
“…65 In addition, in vivo and in vitro studies have suggested that the wall shear stress may influence endothelial recovery after denudation. [66][67][68] Although from these studies, the exact relation between these two factors is not clear. If an extreme deviation of shear stress from normal retards endothelial recovery, this could lessen the inhibitory effect of endothelium and thereby enhance intimal proliferation.…”
Section: Relation Between Low Wall Shear Stress and Intimal Thickeningmentioning
confidence: 99%
“…It now is well established that the primary role of hemodynamic forces (mainly shear stress, a frictional force acting at the interface between the flowing blood and the vessel wall), acting through the endothelium, is to cause chronic restructuring of blood vessels (1-6) as well as to initiate blood-vessel formation through a process termed arteriogenesis (7,8). Several in vivo observations suggest that hemodynamic forces modulate endothelial structure and function, which include increased permeability of macromolecules, lipoproteins accumulation, and endothelial cell damage and repair near branch points and bifurcations (2,4,6). More conclusive evidence for the direct effect of hemodynamic forces on endothelial structure and function has come from in vitro studies in which cultured monolayers have been subjected to defined hemodynamic forces in well controlled model systems.…”
mentioning
confidence: 99%